The Psychology and Communication of Climate Change Ignorance - Connor Thompson (The University of Alabama, 2021)
A review of the book: George Marshall, Don't Even Think About It: Why Our Brains Are Wired to Ignore Climate Change. Bloomsbury USA, 2014, 272 pages. ISBN: 9781632861023